2023
DOI: 10.3390/cells12192350
|View full text |Cite
|
Sign up to set email alerts
|

Could an Anterior Cruciate Ligament Be Tissue-Engineered from Silk?

Judith Hahn,
Clemens Gögele,
Gundula Schulze-Tanzil

Abstract: Silk has a long history as an exclusive textile, but also as a suture thread in medicine; nowadays, diverse cell carriers are manufactured from silk. Its advantages are manifold, including high biocompatibility, biomechanical strength and processability (approved for nearly all manufacturing techniques). Silk’s limitations, such as scarcity and batch to batch variations, are overcome by gene technology, which allows for the upscaled production of recombinant “designed” silk proteins. For processing thin fibroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 153 publications
(235 reference statements)
0
2
0
Order By: Relevance
“…The analysis showed that spider silk tissue outperforms ACL, thanks to its exceptional mechanical resistance, as it can withstand stresses of up to 2.5 MPa [ 145 ]. However, only experimental research still exists for the use of fibroin in ACL grafts, without clinical trials [ 25 ], even though research results are very promising [ 146 ]. Scaffolds made of silk that exhibit osteogenic function, interference screws, and tunnel fillers have been prototyped, with further research related to the stimulation of signaling pathways [ 25 ].…”
Section: Applications In Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis showed that spider silk tissue outperforms ACL, thanks to its exceptional mechanical resistance, as it can withstand stresses of up to 2.5 MPa [ 145 ]. However, only experimental research still exists for the use of fibroin in ACL grafts, without clinical trials [ 25 ], even though research results are very promising [ 146 ]. Scaffolds made of silk that exhibit osteogenic function, interference screws, and tunnel fillers have been prototyped, with further research related to the stimulation of signaling pathways [ 25 ].…”
Section: Applications In Tissue Engineeringmentioning
confidence: 99%
“…However, these traditional treatments do not regenerate cartilage, just relieve patients of pain, unlike novel biomaterials with silk fibroin that can mimic the tissue structure and promote cartilage regeneration and new tissue growth [ 10 ]. Ligament tissue regeneration is complex and still under research, whereas silk-based materials show great promise [ 25 ]. For the repair of damaged intervertebral discs by using silk (hydrogels with silk and silk-based scaffolds), preclinical studies have shown excellent results [ 26 ], but clinical studies are still missing.…”
Section: Introductionmentioning
confidence: 99%